Stewart-Bluefarb Acroangiodermatitis in a Case of Parkes-Weber Syndrome - Ghia, Deepti H (Medknow Publications & Media Pvt Ltd, 2014)
Stewart-Bluefarb acroangiodermatitis is the occurrence of pseudo-kaposiform changes with an underlying arterio-venous malformation. Parkes-Weber syndrome is a triad of arterio-venous malformation with varicose veins with bony and soft-tissue hypertrophy involving the extremity. A 13 year-old-female presented with ulcerated growth with bleeding episodes on right leg since past four years. A reddish discoloration over right leg was noticed at four years of age which remained unchanged until nine years of age, after which it showed rapid increase in size along with disproportionate increase in length and girth of right lower limb. Examination revealed hyperpigmented soft verrucous plaque over the right lower one-third of leg, along with presence of ulcers and dilated tortuous veins in the right lower leg with thrill and bruit over the right popliteal and inguinal region. A differential diagnosis of verrucous hemangioma and arterio-venous malformation with pseudo-kaposiform change was considered. Skin biopsy showed multiple fenestrated capillaries with perivascular lymphocyte infiltrate suggestive of capillary malformations. X-ray showed osteolytic defect in right tibia. Duplex ultrasound and magnetic resonance imaging of right leg showed multiple fast flowing small and medium sized arterio-venous malformations of small to moderate size. Thus, on the basis of clinical and radiological features, we made a diagnosis of Stewart-Bluefarb type of acroangiodermatitis with Parkes-Weber syndrome. She was managed conservatively with compression stockings.